Β‐catenin regulates IRF3‐mediated innate immune signalling in colorectal cancer. (13th July 2018) - Ding, Chengming; He, Jun; Zhao, Jun; Li, Junhua; Chen, Jie; Liao, Wenyan; Zeng, Yi; Zhong, Jing; Wei, Chaoying; Zhang, Liming; Zhou, Mei; Jia, Zeming; et al.
Abstract: Objective: β‐catenin is one of the most critical oncogenes associated with many kinds of human cancers, especially in the human CRC. Innate immunity recognizes tumour derived damage‐associated molecular patterns (DAMPs) and primes the anti‐tumour adaptive responses. While the function of β‐catenin in CRC tumourigenesis is well established, its impact on innate immune evasion is largely unknown. The aim of this study is to characterize the role of β‐catenin in inhibiting RIG‐I‐like receptor (RLR)‐mediated IFN‐β signalling in colorectal cancer. Materials and Methods: Immunohistochemical staining and western blotting were conducted to study the expression of β‐catenin, IRF3 and phospho‐IRF3 (p‐IRF3) in CRC samples and cell lines. Plaque assay determining virus replication was performed to assess the regulation of β‐catenin on IFN‐β signalling. The inhibition of β‐catenin on RLR‐mediated IFN‐β signalling was further studied by real‐time analyses and reporter assays in the context of lentiviral‐mediated β‐catenin stably knocking down. Lastly, co‐immunoprecipitation and nuclear fractionation assay were conducted to monitor the interaction between β‐catenin and IRF3. Results: We found that high expression of β‐catenin positively correlated with the expression of IRF3 in CRC cells. Overexpression of β‐catenin increased the viral replication. Conversely knocking down of β‐catenin inhibited viral replication. Furthermore, our data demonstrated that β‐catenin could inhibit the expression of IFN‐β and interferon‐stimulated gene 56 (ISG56). Mechanistically, we found that β‐catenin interacted with IRF3 and blocked its nuclear translocation. Conclusion: Our study reveals an unprecedented role of β‐catenin in enabling innate immune evasion in CRC.